Effects of paclobutrazol and mepiquat chloride on the growth and development of plantain Dominico Hartón (Musa AAB) - Arias-García, Juan Sebastián; Aristizábal-Loaiza, Manuel (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Colombia is the fourth largest producer of plantain in the world, with a harvest of 3,539,252 t. Various biotic and abiotic factors affect yields, including phytoparasitic nematodes that are a major constraint in this crop. For this reason, strategies are being sought to improve the performance of this plant with this cosmopolitan pest. This research evaluated the effect of two hormonal regulators on the growth and development of the Dominico plantain. The experiment design had treatments that were divided plots, where the main plot corresponded to the type of product, and the sub-plot corresponded to the concentrations of paclobutrazol and mepiquat chloride in the different doses: 0, 250 and 500 mg L-1. The experiment unit consisted of ten plants with four replicates. The evaluated variables were plant height, diameter of the pseudostem, number of functional leaves, length and diameter of the roots, number of nematodes and variables for production quality. The two growth regulators reduced the plant height before emergence of the flower; paclobutrazol reduced the height by up to 40%, while mepiquat chloride reduced the height by up to 6.7%. There were no statistical differences in the production per plant, where the production with paclobutrazol was 14 kg/plant and, with mepiquat chloride, was 15 kg/plant. The control was 14.5 kg/plant. The use of growth regulators did not significantly restrict the damage caused by nematodes; however, paclobutrazol performed better as a growth regulator in the Dominico Hartón plants.